Pemanfaatan Gawangan Tanaman Sawit Produktif untuk Produksi Ubijalar (Ipomoea batatas (L) Lam.) - H Agusta; A Setiawan; H Purnamawati; W Atmoko; T Sugiarto; A Rai (Universitas Sebelas Maret, 2006)
The purpose of the study was to test the production capability of 9 sweet potato genotypes under various oil palm shading levels. The field experiment on 7 and 8 year old plantation of oil palm was conducted at Cikabayan Research Station of Bogor Agricultural University from August 2003 to March 2004 and from January 2005 to June 2005. At the first experiment, eight sweet potato genotypes (cultivar Sukuh, cultivar Jago, BB. 96001.2, BB. 97096.4, AB. 94065.10, cultivar IR Melati, BB. 97020.10 and BB. 94572.2) were planted under four oil palm shading levels (90%, 79%, 68% dan 40%). At the second experiment, cultivar Shiroyutaka was planted undershading levels of 92.4%, 90.6%, 89.3%, 86.5%, 0% shading level (100% of sun light transmission) was used as a control at the both experiments.The result showed, that oil palm shading levels from 40%-90% decreased tuber and crown production. Genotype AB. 94065.10 was that most tolerant genotype to oil palm shading. Cultivar Sukuh was medium tolerant. The other genotypes were very susceptible againts the low light transmission stress.